2019
DOI: 10.1017/jfm.2019.19
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence structures and statistics of a supersonic turbulent boundary layer subjected to concave surface curvature

Abstract: Supersonic turbulent flows at Mach 2.7 over concave surfaces for two different curvature radii were investigated and compared with a flat plate turbulent boundary layer using direct numerical simulations. The streamwise velocity reduces in the outer part of the boundary layer due to the compression while it increases near the wall due to curvature, with a higher shape factor for the concave cases. The near wall spanwise streak spacing reduces compared to the flat plate, with large scale streaks and turbulence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(11 citation statements)
references
References 56 publications
1
9
0
1
Order By: Relevance
“…6(c), corresponds to de-stabilization or stabilization of the boundary layer, respectively. This is consistent with the fact that convex curvature stabilizes the boundary layer, whereas concave curvature destabilizes the boundary layer [48,20]. Furthermore, after an initial adjustment, concave curvature leads to increase in the wall friction, heat transfer, and Reynolds stresses as well as it may give rise to Taylor-Görtler like vortices; on the other hand, the convex surface deformation typically results in opposite effects.…”
supporting
confidence: 79%
See 3 more Smart Citations
“…6(c), corresponds to de-stabilization or stabilization of the boundary layer, respectively. This is consistent with the fact that convex curvature stabilizes the boundary layer, whereas concave curvature destabilizes the boundary layer [48,20]. Furthermore, after an initial adjustment, concave curvature leads to increase in the wall friction, heat transfer, and Reynolds stresses as well as it may give rise to Taylor-Görtler like vortices; on the other hand, the convex surface deformation typically results in opposite effects.…”
supporting
confidence: 79%
“…where δ * and θ are the displacement and momentum thicknesses of the boundary layer. A theoretical estimate of the shape factor of an equilibrium supersonic TBL may be obtained by using a power-law relation for the mean velocity of an incompressible TBL [46,20]. For instance, u/u ∞ = (y/δ x ) 1/n gives the velocity profile of a zero pressure gradient incompressible TBL, where n weakly depends on the Reynolds number (Re x ).…”
Section: Modification Of the Boundary Layermentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that, even in the turbulent flow, the boundary layer is destabilized due to the Gortler instability. Sun et al [4] used DNS method to study a supersonic TBL (STBL) in Mach number of 2.7 under the influence of a concave curvature with two curvature radii of 308 and 908 mm. The results of the velocity profiles showed that the velocity decreases in the outer region of the boundary layer, while it increases near the wall.…”
Section: Introductionmentioning
confidence: 99%